Signatures of Hund metal and finite-frequency nesting in Sr 2 RuO 4 revealed by electronic Raman scattering - Blesio, Germán Gabriel (2024)
We investigate the electronic Raman scattering of Sr2⁢RuO4 using a material-realistic dynamical mean-field theory approach. We identify the low-energy Fermi liquid behavior and point out that the enhanced Raman response at higher energies is a fingerprint of Hund metals. These signatures originate in the two-stage coherence of Hund metals and associated quasiparticle “unrenormalization.” In agreement with recent experimental observations, we find the B1⁢ and B2⁢ responses differ, but our calculations suggest a novel interpretation of this dichotomy. The B1⁢ response is dominated by the ⁢ orbital and the B2⁢ response receives contributions from all orbitals and is strongly affected by previously unnoticed finite-frequency interband nesting. We calculate the vertex-corrections to Raman response and show that their effect is nonvanishing but small.